There is not enough information
In order to help explain how you came to your answer. It also helps when marking or reviewing because it's easier to find any mistakes
Question
x+5/x+2 - x+1/x²+2x
Answer:
= (x² - 4x - 1)/[x (x+2)]
= (x² - 4x - 1)/[x² + 2x]
Step-by-step explanation:
x + 5/x + 2 - x + 1/x² + 2x
We factorise the second denominator to give us :
x + 5/x + 2 - x + 1/x(x + 2)
We find the L.C.M of both denominators which is x(x+2).
[x(x + 5)-(x + 1)] / (x (x + 2))
Expand the bracket
=[x² +5x - x -1] / [x (x + 2)]
=(x² - 4x - 1) / [x (x + 2)]
= (x² - 4x - 1)/ [x (x + 2)]
= (x² - 4x - 1) / [x² + 2x]
Answer:
c. 138 feet
Step-by-step explanation:
h(t) = −16t^2 + 83t + 33
At3 seconds
h(3) = -16(3^2) + 83(3) + 33
h(3) = -16(9) + 249 + 33
h(3) = -144 + 249 + 33
h(3) = 138
c. 138 feet
Equation: y = 1.5x + 3
10.50 = 1.5x + 3
1.5x = 7.5
x = 5
She played 5 games